Weaving in the life of antalya yoruks - Zaymoglu O. , Zaymoglu O. (Рroblems of engineering and professional education, 2023)
The article contains information about knitting technology. Weavings are technically divided into two as pile and pile-free. Rugs, which are included in the group of pile-free weavings within this basic distinction, constitute the cornerstones of Turkish weaving culture. Being the most basic surface creation technique that can be made with weft and warp thre adsand then diversified with additional weft / pattern thre adsusedf or pattern purposes, it is included under the heading of plain weaving.Rugs, as intangible cultural heritage items, show another facet of Turkish weaving. Within the scope of thestudy, kilims, whichare an importantpart of the Yörük culture, werediscussed in thedistricts of Aksu (YurtpınarTown), Döşemealtı, Elmalı, Gazipaşa, Kaş, Kepez (Varsak Town), Korkuteli and Manavgat. It is possibletofindtraces of Yörük culture in almosteverydistrict of Antalya. Due to the point this culture has reached today, it is seen that the weaving culture has largely disappeared. It is seenthatthe main reasons forthedisappearance of then omadic culture are the opportunitiesoffered by tourisman deasyliving conditions. It is seen that then omadsarealsoforcedin to settled life as a policy of the administration. The disappearance of the immigrationsituation directlyaffectedtheneed for rugs. The rug samples, which are light, easily transportable, and meet many needs with their usageareas, can be obtained from the houses of the villagers, the samples left in the hands of the merchants, and the museums. As in all weavings, the existence of regional Anatolian rich motifs, patterns, compositions and color features is revealed in rugs.